Advanced-stage pancreatic cancer: therapy options - Werner, Jens; Combs, Stephanie; Springfeld, Christoph; Hartwig, Werner; Hackert, Thilo; Büchler, Markus W. (Nature reviews. Clinical oncology, 2013)
Although surgery is a requirement for a potential cure from pancreatic cancer, it is usually diagnosed at a late stage, when surgical intervention is not straightforward. This Review article outlines the controversies surrounding the treatment options for patients with advanced-stage pancreatic cancer, from surgery through to chemotherapy, radiotherapy, targeted agents and palliative care.
Gesehen am 04.11.2021